THE RIGHT TO DEVELOP A TRAFFIC SAFETY CULTURE AMONG STUDENTS IS THE FOUNDATION OF SOCIETY - Akhmedov Akmal Bakhtiyorovich (European Journal of Humanities and Educational Advancements, 2024)
In this article, the important features of the development of traffic safety culture among students, the creation of a preventive system in educational institutions, the maintenance of the mental and spiritual health of boys and girls, and the development of their traffic safety culture. a general analysis of theoretically based approaches to the issues of wide implementation and promotion of educational programs is described.